Pelatihan Kader Dalam Penanganan Hipertensi: Optimalisasi Terapi Daun Sirsak Sebagai Bentuk Konservasi Yang Berbasis Kearifan Lokal - Rosdiana, Nina; Suleman, Happy Kurniati; Rosita, Sinta; Asiah, Selina Nur (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Background As age increases, the body undergoes many changes, both in terms of physical and psychological. Striking changes are physical changes which often cause health problems are changes in the cardiovascular system. One of them is hypertension which often occurs in the elderly. Based on data from the Ciamis Regency Health Office, there are around 640 elderly people experiencing hypertension in Cipaku sub-district. Hypertension is a lifelong disease, so it needs to be treated and maintained so that blood pressure is always in a normal state. One of them is by using alternative therapy of soursop leaf decoction water which in the Ciamis area itself has many soursop trees. The object of this service is health cadres in the Ciamis district area as many as 30 cadres. The method of this service is to provide training to cadres about soursop leaf decoction water and its impact on blood pressure. The results showed that the cadres' knowledge became better after being given this training with a picture of knowledge with an increase of 26.0. Conclusions Soursop leaf decoction water can be used as an alternative therapy in maintaining normal blood pressure. therapy in maintaining normal blood pressure.